1999
DOI: 10.1093/protein/12.3.251
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of active-site aromatic residues in xylanase A from Streptomyces lividans

Abstract: The role of four aromatic residues (W85, Y172, W266 and W274) in the structure-function relationship in xylanase A from Streptomyces lividans (XlnA) was investigated by site-directed mutagenesis where each residue was subjected to three substitutions (W85A/H/F; W266A/H/F; W274A/H/F and Y172A/F/S). These four amino acids are highly conserved among family 10 xylanases and structural data have implicated them in substrate binding at the active site. Far-UV circular dichroism spectroscopy was used to show that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 20 publications
5
25
0
1
Order By: Relevance
“…On the other hand, iXylC was completely inactivated by Trp residue-specific chemical modifiers such as 1 mM Hg 2+ and 5 mM N-bromosuccinimide, as had also been demonstrated in many other xylanases (Cheng et al, 2008;Li et al, 2008). These results correspond to the demonstration that some Trp residues in the active site of extracellular GH10 xylanases play a key role in catalysis and/or substrate-binding (Roberge et al, 1999;Zolotnitsky et al, 2004). The significant inhibition (>40% of original activity) of iXylC activity was also noted in the presence of 1 mM Cu 2+ , 5 mM EDTA, and 5 mM N-ethylmaleimide.…”
Section: Enzymatic Properties Of Ixylcsupporting
confidence: 80%
See 1 more Smart Citation
“…On the other hand, iXylC was completely inactivated by Trp residue-specific chemical modifiers such as 1 mM Hg 2+ and 5 mM N-bromosuccinimide, as had also been demonstrated in many other xylanases (Cheng et al, 2008;Li et al, 2008). These results correspond to the demonstration that some Trp residues in the active site of extracellular GH10 xylanases play a key role in catalysis and/or substrate-binding (Roberge et al, 1999;Zolotnitsky et al, 2004). The significant inhibition (>40% of original activity) of iXylC activity was also noted in the presence of 1 mM Cu 2+ , 5 mM EDTA, and 5 mM N-ethylmaleimide.…”
Section: Enzymatic Properties Of Ixylcsupporting
confidence: 80%
“…Functions of some aromatic amino acid residues, such as His and Trp, conserved in active site of extracellular GH10 xylanases have recently been identified to play an essential role in catalysis and/or substrate-binding of the enzymes by site-directed mutagenesis (Roberge et al, 1999) and mapping of GH substrate sub- sites (Zolotnitsky et al, 2004). However, no study has yet been reported on functional characterization of active site aromatic residues conserved in intracellular GH10 xylanases, which are expected to have distinct substrate specificity compared to extracellular GH10 enzymes.…”
Section: Site-directed Mutagenesis Of Trp Residuesmentioning
confidence: 99%
“…The rXylK1 was relatively unaffected by sulfhydryl reagents (5 mM) such as sodium azide, iodoacetamide, and N-ethylmaleimide, while the enzyme lost 68% of its original activity when preincubated with 5 mM EDTA for 10 min. The complete inhibition of rXylK1 by 5 mM N-bromosuccinimide was in good agreement with the fact that three Trp residues in the highly conserved region of the GH10 enzymes are critically involved in enzyme-substrate interaction, as shown for Streptomyces lividans (16) and Geobacillus stearothermophilus T-6 (18) GH10 xylanases. It was predicted that the three residues Trp118, Trp306, and Trp314 in premature XylK1 might be responsible for catalysis and substrate binding of the enzyme.…”
supporting
confidence: 80%
“…Unlike Family 10 xylanases, the native Xyn2 protein has no stabilizing disulfide bridges or N-terminal thermostabilizing domain [14] , however, the aromatic residues in xylanase were found to be responsible for its thermal stability. When additional aromatic interaction was introduced into Family 11 xylanase, the thermostability of the enzyme was improved [15,16] . Furthermore, the N-terminal fusion peptide (51 amino acids) may also play a role in stabilizing its righthand ␤ -sandwich structure.…”
Section: Discussionmentioning
confidence: 99%